2015
DOI: 10.1016/j.rmcr.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in idiopathic nonspecific interstitial pneumonia after smoking cessation

Abstract: Although cigarette smoking has been recognized as a risk factor for the development of several interstitial lung diseases, the relationship between smoking and nonspecific interstitial pneumonia (NSIP) has not yet been fully elucidated. We here present a case of fibrotic NSIP with mild emphysema in an elderly male with normal pulmonary function, whose symptoms, serum KL-6 level, and high-resolution computed tomography findings of interstitial changes markedly improved without medication following the cessation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Similarly, honeycombing, which is common in IPF is rarely found in NSIP [199]. Additionally, NSIP progression is slow with some cases even reporting regression of disease [197,200]. Lastly, 5 years post diagnosis, 80-85% survival is reported indicating much better outcomes than IPF [129].…”
Section: Idiopathic Nonspecific Interstitial Pneumoniamentioning
confidence: 99%
“…Similarly, honeycombing, which is common in IPF is rarely found in NSIP [199]. Additionally, NSIP progression is slow with some cases even reporting regression of disease [197,200]. Lastly, 5 years post diagnosis, 80-85% survival is reported indicating much better outcomes than IPF [129].…”
Section: Idiopathic Nonspecific Interstitial Pneumoniamentioning
confidence: 99%
“…In our study it is observed that among the smokers the most common pattern is UIP. However studies shows that NSIP(Nonspecic Interstitial Pneumonia) pattern associated with smoking has a good (20) prognosis . Spirometry shows restrictive pattern in all 10 cases and (21,22) are consistent with other studies by Dawson et al and Banks J et al .…”
Section: Resultsmentioning
confidence: 99%
“…5) [32]. Some authors have proposed that smoking is closely related to NSIP-pattern fibrosis [33,34].…”
Section: Relationship Between Non-specific Interstitial Pneumonia Andmentioning
confidence: 99%